Psychological counseling, rights protection, and dispute prevention of sports vulnerable groups - Xiheng Zhang; Ping Wang , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The psychological difficulties of college students are researched, and sports events are employed as a kind of intervention aimed at disadvantaged groups of college athletes. As a sample, 300 poor college students from six universities in Shanghai, China, were selected as the intervention group, whereas 300 college students were randomly selected as the control group. Symptom Checklist 90 examined 10 mental health indicators (SCL-90). The intervention group designed a sports game program as an intervention. The detection rate of mental health disorders among vulnerable college student groups was 76.33 percent, compared to 25.33 percent in the control group. Before the intervention, the scores of female students in the intervention group on interpersonal relationships, depression, anxiety, hostility, and other factors were significantly higher than those of male students in the intervention group. Still, after the intervention, there was no significant difference. The study concluded that the intervention of sports games could improve the mental health of vulnerable college students, particularly in terms of hostile variables. The effect on girls is more significant than that on boys.